Information Modeling Procedure to Represent a Territory Affected by Earthquake (diségno, 2018)
ARIM (Assessment Reconstruction Information Modeling) procedure can be seen as the evolution and integration of the BIMsystems used so far to monitor and document the transformations of the territory, such as HBIM, GeoBIM, LIM and SeismicBIM,representing at the same time their natural evolution for the management of prevention and reconstruction connected to naturaldisasters.The application of the procedure is described on the case study of a building aggregate of Grisciano, a borough of the Municipalityof Accumoli, describing the steps that constitute the part of the design/reconstruction of the BIM procedure, consisting of: cognitiveframework, distinguished in ‘direct knowledge’ and ‘deferred knowledge’; processing of the data collected; framework of the ARIMprocedure, which provides a sub-articulation in data acquisition and their synthesis, finally the construction of the synthetic andinformed 3D model.
Keywords: BIM; ARIM; 3D modeling; earthquake; VPL